Impact of electric trucks powered by overhead lines on the European electricity system and CO2 emissions. (July 2019) - Plötz, Patrick; Gnann, Till; Jochem, Patrick; Yilmaz, Hasan Ümitcan; Kaschub, Thomas
Abstract: Despite the comparatively limited stock of vehicles, heavy-duty road transport is responsible for a major share of CO2 emissions from the European transport sector. Electric trucks powered by overhead lines, so-called trolley trucks or catenary hybrid trucks, have been proposed as a potential GHG mitigation option. However, from the perspective of the energy system, trolley trucks constitute an additional and inflexible electricity demand. Here, we analyse scenarios with an ambitious European market diffusion of trolley trucks and their impact on the electricity system and CO2 emissions. Our results show that trolley trucks can noteworthily reduce the CO2 emissions from heavy road transport even when the additional CO2 emissions from electricity generation are taken into account. Furthermore, the actual impact of the additional load from trolley trucks on the total energy system is limited. Compared to the anticipated electricity demand from passenger cars in 2030, trolley trucks require less energy and the load is more equally distributed over daytime. Our findings thus show that electric trucks are an interesting option for CO2 mitigation in heavy road transport. Highlights: Market diffusion scenarios of electric trucks in Europe. CO2 emissions from trucks in transport in energy sector are covered. Load curves for trolley trucks are introduced. A full energy system analysis including trolley trucks is run. Electric trucks reduce CO2 emissions from the transport and energy sector.